2018
DOI: 10.1111/bph.14193
|View full text |Cite
|
Sign up to set email alerts
|

Treatment withIL‐19improves locomotor functional recovery after contusion trauma to the spinal cord

Abstract: IL-19 treatment reduced secondary injuries and improved locomotor functional recovery after contusion SCI, through diverse mechanisms including immune cell polarization, angiogenesis and anti-oxidative responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…In addition, Lu et al had verified that fibroblast growth factor 21 improved functional recovery and axonal regeneration through regulating oxidative stress after PNI [59]. Reducing excessive oxidative stress improves the locomotor functional recovery after SCI [60]. One previous study has also demonstrated that metformin restores mitochondrial biogenesis by inhibiting of the PDK4/oxidative stress-mediated apoptosis pathway [61].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lu et al had verified that fibroblast growth factor 21 improved functional recovery and axonal regeneration through regulating oxidative stress after PNI [59]. Reducing excessive oxidative stress improves the locomotor functional recovery after SCI [60]. One previous study has also demonstrated that metformin restores mitochondrial biogenesis by inhibiting of the PDK4/oxidative stress-mediated apoptosis pathway [61].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the decreased plasma IL-17 and IL-23 level in survivors implicate a remarkable reduction of organ injury induced by ischemia, whereas the elevation of IL-17 in non-survivors suggests an aggravation of ischemic injury. It should be noted that several other interleukins such as IL-19 and IL-21 also contribute to myocardial injury during ischemia [57][58][59], so we may need more investigation on them in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we examined whether exogenous IL-19 abolishes the effect of IL-19 deficiency in EAE. According to the previous studies showing that the daily administration of IL-19 protein (10 ng/g of body weight) can offset IL-19 deficiency ( 29 , 30 ), we firstly treated WT and IL-19 −/− EAE mice with recombinant mouse IL-19 protein (10 ng/g of body weight) or PBS by intraperitoneal injection every day. However, even daily injection with PBS caused mice severe stress which markedly suppressed EAE development ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mice were intraperitoneally injected with 200 ng pertussis toxin on days 0 and 2 post-immunization. To investigate the effect of IL-19, EAE mice were treated with mouse recombinant IL-19 protein (20 ng/g of body weight) by intraperitoneal injection every other day starting on day 2 post-immunization, according to a modification of a previously reported method ( 29 , 30 ). The mice were assessed daily for clinical signs of EAE, according to the following grading system: 0, normal; 1, limp tail or mild hind limb weakness; 2, moderate hind limb weakness or mild ataxia; 3, moderate to severe hind limb weakness; 4, severe hind limb weakness, mild forelimb weakness or moderate ataxia; 5, paraplegia with moderate forelimb weakness; and 6, paraplegia with severe forelimb weakness, severe ataxia, or moribundity.…”
Section: Methodsmentioning
confidence: 99%